USULAN PENINGKATAN KUALITAS PELAYANAN MENGGUNAKAN QUALITY FUNCTION DEPLOYMENT BERBASIS SERVICE QUALITY DAN KANO MODEL PADA BARBERSHOP HAX - Fauzy, Devan Nur (JUSTI (Jurnal Sistem dan Teknik Industri), 2023)
Service quality is the effort to meet customer needs and expectations and evaluate them based on their perceptions, while customer satisfaction arises from comparing perceived performance with expectations for a product or service. This study aims to identify and analyze the service quality of Barbershop HAX using Quality Function Deployment (QFD) and integrating the Service Quality (Servqual) method with the Kano Model. The Servqual method measures the gap between customer expectations and perceptions of service, while the Kano Model categorizes service attributes based on their impact on customer satisfaction. Analysis of 27 service attributes revealed that overall, customer perceptions were lower than their expectations, indicating a gap between customer expectations and the reality of the service provided. The study results in a structured and systematic proposal for improvement based on data processing, utilizing activity network diagrams to plan the sequence and prioritize implementation of each improvement step.